2020
DOI: 10.1101/2020.10.19.345355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Child abuse associates with increased recruitment of perineuronal nets in the ventromedial prefrontal cortex: a possible implication of oligodendrocyte progenitor cells

Abstract: Child abuse (CA) is a strong predictor of psychopathologies and suicide, and can lastingly alter normal trajectories of brain development, particularly in areas closely linked to emotional responses such as the prefrontal cortex (PFC). Yet, the cellular underpinnings of these enduring effects are unclear. Childhood and adolescence are marked by the protracted formation of perineuronal nets (PNNs), which are essential in orchestrating the closure of developmental windows of cortical plasticity by regulating the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
(98 reference statements)
1
13
0
Order By: Relevance
“…Along with the augmented density of PNNs, the authors observed an increase in intensity of the staining and coverage of enwrapped cells ( Figure 4 ) that was associated with child abuse. Using in situ hybridization, the same study found that 65% of vmPFC PV-positive cells were surrounded by PNNs in psychiatrically healthy controls ( Tanti et al, 2020 ) which is similar to the ratio calculated in rodent studies using IHC ( Van’t Spijker and Kwok, 2017 ). The ratio of neurons enwrapped by PNNs was disturbed in depressed suicides with a history of child abuse.…”
Section: Early Life Stress Modulates Local Amygdala Circuits and Inhibitory Interneuronssupporting
confidence: 74%
See 2 more Smart Citations
“…Along with the augmented density of PNNs, the authors observed an increase in intensity of the staining and coverage of enwrapped cells ( Figure 4 ) that was associated with child abuse. Using in situ hybridization, the same study found that 65% of vmPFC PV-positive cells were surrounded by PNNs in psychiatrically healthy controls ( Tanti et al, 2020 ) which is similar to the ratio calculated in rodent studies using IHC ( Van’t Spijker and Kwok, 2017 ). The ratio of neurons enwrapped by PNNs was disturbed in depressed suicides with a history of child abuse.…”
Section: Early Life Stress Modulates Local Amygdala Circuits and Inhibitory Interneuronssupporting
confidence: 74%
“…To our knowledge, a single study has examined the possible consequences of ELS on PNNs in human post-mortem tissue. This recent paper reported an increase in PNNs in layers III, IV, V, and VI of the vmPFC of adult depressed suicides with a history of severe child abuse ( Tanti et al, 2020 ). Along with the augmented density of PNNs, the authors observed an increase in intensity of the staining and coverage of enwrapped cells ( Figure 4 ) that was associated with child abuse.…”
Section: Early Life Stress Modulates Local Amygdala Circuits and Inhibitory Interneuronsmentioning
confidence: 96%
See 1 more Smart Citation
“…PNNs are established during postnatal development and their maturation is intimately associated with the opening and closure of critical periods of enhanced neuroplasticity ( Wen et al., 2018 ). Recent evidence suggests that PNNs on PV neurons may be altered by early life stress in animals ( Gildawie et al., 2019 ; Mukhopadhyay et al., 2021 ) and humans ( Tanti et al., 2020 ), which are thought to reflect changes in PV cell excitability, plasticity, oxidative stress, and other metabolic functions ( Wen et al., 2018 ). PNNs are typically labeled using a lectin called Wisteria floribunda lectin (WFL) or agglutinin (WFA), which binds a carbohydrate residue found in PNNs, in particular those surrounding PV neurons.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, perineuronal nets (PNNs) have heightened affinity to PV-expressing GABAergic interneurons, and PNN formation and condensation is thought to coincide with the closure of critical periods ( Reichelt et al, 2019 ). New evidence suggests that CA might be associated with increased recruitment and maturation of PNNs in human ventromedial prefrontal cortex as well as with upregulated expression of canonical components of PNNs in oligodendrocyte progenitor cells ( Tanti et al, 2020 ). Despite these findings, it has been demonstrated that PNNs may also be dynamically regulated in adulthood, in processes such as learning and memory formation ( Banerjee et al, 2017 ; Carulli et al, 2020 ).…”
Section: Molecular Impacts Of Camentioning
confidence: 99%